The influence of the Sustainable Seafood Movement in the US and UK capture fisheries supply chain and fisheries governance - Gutiérrez, Alexis T.; Morgan, Siân K. (Frontiers in Marine Science, 2015)
Over the last decade, a diverse coalition of actors has come together to develop and promote sustainability initiatives ranging from seafood eco-labels, seafood guides, traceability schemes, and sourcing policies in Western seafood supply chains. Based on a literature review, we trace the development of the Sustainable Seafood Movement, which has been working to reform sustainability practices in the seafood supply chain. Focusing on the US and the UK capture fisheries, we explore the roles of key actors and analyze the dynamics within and between actor groups through a conceptual model derived from semi-structured interviews. We argue that the Sustainable Seafood Movement is different from previous social movements in that, in addition to actors advocating for government reform, it has motivated supply chain actors to participate in non-state market driven governance regime. The movement and its actors have leveraged their legitimacy and authority garnered within the supply chain to increase their legitimacy and authority in public governance processes. As the movement continues to evolve, it will need to address several emerging issues to maintain its position of legitimacy and authority in both the supply chain and public governance processes.